Optimization of net revenue of rice production in Pampanga river basin - David, Maria Cristina V.; Tabios, Guillermo Q. III (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
This study involves using water resources simulation model with optimization of rice production in the Pampanga River Basin. Fundamentals of irrigation system operation both in reservoir and farm levels are reviewed from the perspective of describing the physical process and also, in the context of optimization, defining typical decision problems and associated decision variables. The developed and adopted crop yield prediction models were applied to simulate the response of rice crop as a function of the amount irrigation water applied and other parameters which were weather and agronomic variables. The output of this study is a useful tool for planning agricultural hydrosystem on efficient and optimal use of water irrigation supply for agricultural production. Agricultural production is always related to business operation so that this study demonstrates how irrigation management can be appraised from a business perspective so that the objective function of the optimization conducted tool in this study is based on maximize net revenue. Finally, the output of this study can result to self-sufficiency in rice production and elevate the socio-economic status of the farmers.
Thesis (Doctor of Philosophy in Civil Engineering)--University of the Philippines Diliman
Keywords: Mathematical optimization; Crop yields -- Forecasting; Rice -- Irrigation; Agricultural hydrosystem